DINAMIKA SOSIAL-EKONOMI PETANI TEMBAKAU DI INDONESIA: STUDI KESEJAHTERAAN DAN KEBERLANJUTAN - YAqin, Abdullah; Ridho, Muhammad Izul; Uluf, Wilda Tul (LPPM Sekolah Tinggi Agama Islam Al-Utsmani Bondowoso, 2025)
Tobacco farmers in Indonesia face a variety of complex socio-economic challenges, especially related to their welfare and sustainability of their farming. The welfare of tobacco farmers as producers of cigarette raw materials is not comparable to their contribution to state revenues from cigarette excise. This study aims to analyze the socio-economic dynamics that affect the welfare of tobacco farmers in Indonesia. In addition, this study aims to identify factors that support or hinder the sustainability of tobacco farming businesses. Case studies are used to analyze data related to the welfare of tobacco farmers in Indonesia. This study successfully found; Crop diversification has a positive impact on the economic conditions of tobacco farmer families, such as increasing work productivity and reducing debt traps. The government provides support to tobacco farmers through technical assistance, training, access to modern equipment, and agricultural technology innovations to increase productivity and efficiency. However, tobacco farmers' access to Tobacco Excise Revenue Sharing Funds (DBH CHT) for crop diversification is still minimal and the types of assistance provided are not necessarily in accordance with the needs of farmers in the field. Further research is needed to understand how government policies can be optimized to improve the welfare of tobacco farmers and ensure the sustainability of tobacco farming in Indonesia.